Rubicon-Dependent Lc3 Recruitment to Salmonella-Containing Phagosomes Is a Host Defense Mechanism Triggered Independently From Major Bacterial Virulence Factors - Masud, Samrah; van der Burg, Lars; Storm, Lisanne; Prajsnar, Tomasz K.; Meijer, Annemarie H. (Frontiers in Cellular and Infection Microbiology, 2019)
Intracellular pathogens such as Salmonella depend on their molecular virulence factors to evade host defense responses like autophagy. Using a zebrafish systemic infection model, we have previously shown that macrophages target Salmonella Typhimurium by an autophagy-related pathway known as Lc3-associated phagocytosis (LAP), which is dependent on the host protein Rubicon. Here, we explore the influence of Salmonella virulence factors on pathogenicity in the zebrafish model and induction of LAP as a defense response. We investigated five mutant strains that all could trigger GFP-Lc3 recruitment as puncta or rings around single bacteria or bacterial clusters, in a Rubicon-dependent manner. We found that S. Typhimurium strains carrying mutations in PhoP or PurA, responsible for adaptation to the intracellular environment and efficient metabolism of purines respectively, are attenuated in the zebrafish model. However, both strains show increased virulence when LAP is inhibited by knockdown of Rubicon. Mutations in type III secretion systems 1 and 2 factors, SipB and SsrB, which are important for invading and replicating in non-phagocytic cells, did not affect the ability to establish successful infection in the zebrafish model. This observation is in line with our previous characterization of this infection model revealing that macrophages actively phagocytose the majority of S. Typhimurium. In contrast to SipB mutants, SsrB mutants were unable to become more virulent in Rubicon-deficient hosts, suggesting that type III system 2 effectors are important for intracellular replication of Salmonella in the absence of LAP. Finally, we found that mutation of FlhD, required for production of flagella, renders S. Typhimurium hypervirulent both in wild type zebrafish embryos and in Rubicon-deficient hosts. FlhD mutation also led to lower levels of GFP-Lc3 recruitment compared with the wild type strain, indicating that recognition of flagellin by the host innate immune system promotes the LAP response. Together, our results provide new evidence that the Rubicon-dependent LAP process is an important defense mechanism of macrophages against S. Typhimurium.